The Green Hotel Paradox: Understanding Managerial Tensions Between Sustainability and Business Performance - Naufal Fawwaz; Ignatius Hari Santoso (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
The increasing demands on the hotel industry to implement sustainable practices create challenges for hotel managers in balancing environmental goals and business performance. This situation has given rise to the green hotel paradox, a situation where hotels must meet sustainability demands without neglecting business targets. This study aims to understand the dynamics of this managerial tension through the perspective of Paradox Theory by examining the influence of paradox mindset, environmental sustainability orientation, and business performance pressure on perceived tension, as well as their impact on green innovation strategy and sustainable performance. The study used a quantitative approach, surveying 102 hotel managers in various tourist cities in Indonesia. Data were collected using a questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that paradox mindset, environmental sustainability orientation, and perceived tension positively influence the relationships tested. Green innovation strategy has also been shown to improve sustainable performance. However, business performance pressure has no significant effect on perceived tension. This study extends the application of Paradox Theory to the context of green hotels and emphasizes the importance of developing a paradox mindset and green innovation strategy to support organizational sustainability.